Perspektiven für die wichtigsten von der deutschen Fischerei genutzten Bestände für 1996 - Dornheim, Holger (1996)
This article informs about the current status and development of fish stocks which are•of commercial importance for all branches of the German fisheries in the•entire North Atlantic. The information is based to a large extent on the reports of the Advisory Committee on Fishery Management (ACFM)of the International Council of the Sea(ICES) and in close connection with the results of scientific investigations of different institutes in Europe dealing with fish including the Institute for Sea Fisheries in Hamburg. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010.